2019
DOI: 10.3390/medicina55060243
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Index for Nonalcoholic Steatohepatitis—HUFA—Based on Routinely Performed Blood Tests

Abstract: Background and objectives: Data suggests that nearly 30% of the general population have steatosis and up to 5% of this population develops nonalcoholic steatohepatitis (NASH). Liver biopsy is still considered to be the gold standard for the diagnosis of NASH. Great effort is being made toward the identification of sensitive diagnostic tests that do not involve invasive procedures to address a common concern in patients with the nonalcoholic fatty liver disease—whether they have NASH or simple steatosis. We aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Its level in blood can increase with insulin resistance, atherosclerosis, hypertension, and obesity. The factors resulting in this relationship are hypothesized to be inflammation and oxidative stress [9,26]. Moreover, an increasing amount of data suggests a link between UA and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its level in blood can increase with insulin resistance, atherosclerosis, hypertension, and obesity. The factors resulting in this relationship are hypothesized to be inflammation and oxidative stress [9,26]. Moreover, an increasing amount of data suggests a link between UA and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an increasing amount of data suggests a link between UA and NAFLD. Many recent observations were done in order to elaborate on this connection [8,9,13,26,27,28,29]. It can be said that this connection is strengthened by studies that used xanthine oxidase inhibitors on animals in order to decrease UA production.…”
Section: Discussionmentioning
confidence: 99%
“…14 Non-alcoholic fatty liver disease (NAFLD) is a serious manifestation of visceral fat accumulation. 15,16 In 1,365 obese adults, Liu et al reported that SUA level independently correlated with the risk of NAFLD. 17 After 6 years of follow-up in 14,442 healthy adults, Yang et al found that 29.2% of participants developed new metabolic diseases with NAFLD being the main risk factor.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from lipogenesis and dyslipidemia, the pathogenesis of NAFLD was closely linked to oxidative stress and inflammation ( Culafic et al., 2019 ). A close positive correlation exists between the total antioxidant capacity of the body’s defense system and health ( Zhang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%